Spatial analysis of subway passenger traffic in Saint Petersburg - Baltyzhakova, Tatiana; Romanchikov, Aleksei (Geodesy and Cartography, 2021)
The purpose of the paper is to create clear visualization of passenger traffic for Saint Petersburg subway system. This visualization can be used to better understand the passenger flow and to make more informed decisions in future planning. Research was based on officially published information about passenger traffic on subway station for years 2016 and 2018. Visualization was created with the variety of methods and software: Voronoi diagrams (QGIS software), social gravitation potential (R programming language), presentation of gravitation potential as a relief (Blender software), service zones of ground transport accessibility (2GIS, QGIS and Mapbox mapping platform). In this research, authors propose the use of intersection between the service zones and social gravitation potential isolines as an instrument for spatial analysis of traffic data. Analysis shown that current development of subway system does not correspond to passenger distribution. All stations were classified according to their accessibility and propositions about future directions of development were made.